2017
DOI: 10.1080/21691401.2017.1373657
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and antioxidant properties of Lycium barbarum polysaccharides capped selenium nanoparticles using tea extract

Abstract: Selenium nanoparticles (SeNPs) have attracted increasing interest over the last decades because of their activities on redox balance in human body. However, the SeNPs tend to aggregate into large clusters, resulting in lower bioactivity, bioavailability and biocompatibility. Surface-capping agents on SeNPs play crucial roles in its stabilization and biological activity. Here, a green synthesis method for the preparation of Lycium barbarum polysaccharides capped SeNPs using green tea extracts as reductants unde… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
69
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 118 publications
(77 citation statements)
references
References 35 publications
8
69
0
Order By: Relevance
“…Similarly, XRD pattern also revealed the amorphous nature of nSe ( figure 3(e)). The pattern depicted a broad 2θ diffraction peak at 23.30°in accordance with the previouly documented literature [45,48,49]. Raman spectrum of nSe in the range of 150 to 600 cm −1 exhibited a prominent resonance peak at 253 cm −1 owing to Se-Se stretching vibrations, confirming the amorphous nature of nSe ( figure 3(f)) [46,[50][51][52].…”
Section: Resultssupporting
confidence: 87%
See 2 more Smart Citations
“…Similarly, XRD pattern also revealed the amorphous nature of nSe ( figure 3(e)). The pattern depicted a broad 2θ diffraction peak at 23.30°in accordance with the previouly documented literature [45,48,49]. Raman spectrum of nSe in the range of 150 to 600 cm −1 exhibited a prominent resonance peak at 253 cm −1 owing to Se-Se stretching vibrations, confirming the amorphous nature of nSe ( figure 3(f)) [46,[50][51][52].…”
Section: Resultssupporting
confidence: 87%
“…The size distribution histogram of nSe as obtained from TEM indicated the average particle size of nSe was ∼50.02 nm (figure S4). The nSe synthesized previously using other plant extracts showed larger particle sizes such as from Withania somnifera (45-90 nm ) [45], Lycium barbarum (125 nm) [47]. On the other hand, Kokila et al demonstrated smaller size (4-16 nm) of nSe using Diospyrosmontana, but they were stable only upto 15 days [30].…”
Section: Resultsmentioning
confidence: 97%
See 1 more Smart Citation
“…Briefly, Lycium barbarum sourced from Ningxia province of China was first boiled at 80 °C for 30 min and then soaked for 30 min. The resulting soup was subsequently concentrated by the soaking extracting method [ 47 , 48 ]. The technical bulletin stated that the final powder product contained a standardized 3.5% LBP while the remaining ingredients were mostly lactose.…”
Section: Methodsmentioning
confidence: 99%
“…The use of elemental Se in the form of NPs for different biological applications gained a lot of attention lately, because of several proposed advantages compared with other forms of Se, including higher bioavailability [ 98 ], lower toxicity [ 41 , 99 , 100 , 101 ], potential for local delivery of high doses into cancer cells [ 102 ]; possibility to be modified, stabilized and functionalized by various polymers such as chitosan [ 103 , 104 , 105 , 106 ] or other polysaccharides [ 107 , 108 , 109 , 110 , 111 , 112 ], proteins [ 113 , 114 ], or even combinations between them [ 115 , 116 , 117 ], smaller molecules such as polyphenols [ 118 , 119 , 120 , 121 ], sialic acids [ 122 , 123 ], folic acid or folate (as folate–chitosan smart-shell nanocapsules) [ 124 , 125 , 126 ], and other organic acids [ 37 ]. Chemical, physical, or biological methods are used for producing SeNPs [ 37 ], each having its own advantages and disadvantages.…”
Section: Conventional and Next-generation Selenium Dietary Supplemmentioning
confidence: 99%